Odpowiedzi

Najlepsza Odpowiedź!
2010-03-29T17:41:21+02:00
5x - 3 + 2x = 4x +9 - x
7x-3=3x+9
4x=12
x=3

12 - 7x + 8x - 18 = 3x - 8
x-6=3x-8
-2x=-2
x=1

7 ( 4x + 3 ) - 6 ( 5x + 7 ) = 0
28x+21-30x-42=0
-2x=21
x= -10,5

4z - 3 (8z + 1 ) - 5 (4 - 3z ) = -1 +2 ( 4 - 5z )
4z-24z-3-20+15z= -1+8-10z
-5z-23= -10z+7
5z= 30
z= 6

2 (9x - 1 ) -3 ( 2x +1 ) + 4 = 5 ( 4x + 3 )
18x-2-6x-3+4= 20x+15
-8x=16
x= -2
1 5 1
2010-03-29T17:42:26+02:00
5x - 3 + 2x = 4x +9 - x
4x=11
x=2,75


12 - 7x + 8x - 18 = 3x - 8
2x=2
x=1


7 ( 4x + 3 ) - 6 ( 5x + 7 ) = 0
28x+21 - 30x -35=0
2x=14
x=7


4z - 3 (8z + 1 ) - 5 (4 - 3z ) = -1 +2 ( 4 - 5z )
4z-24z-3-20+15z=-1+8-10z
5z=27
z=5,4


2 (9x - 1 ) -3 ( 2x +1 ) + 4 = 5 ( 4x + 3 )
18x-2-6x-3+4=20x+15
-8x=16
x=-2

2x/3 - 3x/4 - 1/6 = 1 |*12
8x-9x-2=12
x=-14

2010-03-29T18:07:01+02:00
5x - 3 + 2x = 4x +9 – x
5x+2x-4x+x=9+3
4x=12 |:4
X=3

12 - 7x + 8x - 18 = 3x – 8
-7x+8x-3x=-8-12+18
-2x=-2 |*(-1)
2x=2 |:2
X=1

7 ( 4x + 3 ) - 6 ( 5x + 7 ) = 0
28x+21-30x-42=0
28x-30x=-21+42
2x=21 |:2
X=1o.5

4z - 3 (8z + 1 ) - 5 (4 - 3z ) = -1 +2 ( 4 - 5z )
4z-24z-3-20+15=1+8-10z
4z-24z+10z=1+8+3+20-15
-10z=17 |*(-10)
Z=-17/10
Z=-1 7/10

2 (9x - 1 ) -3 ( 2x +1 ) + 4 = 5 ( 4x + 3 )
18x-2-6x-3+4=20x+15
18x-6x-20x=15+2+3-4
-8x=16 |:(-8)
X=-2